2016
DOI: 10.1016/j.celrep.2015.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Neuronal Receptor Controlling Anaphylaxis

Abstract: Allergic reactions can in severe cases induce a state of circulatory shock referred to as anaphylaxis. Histamine, the primary mediator of this condition, is released from immune cells, and, therefore, anaphylaxis has so far been considered an immune system disorder. However, we here show that the glutamatergic receptor mGluR7, expressed on a subpopulation of both peripheral and spinal cord neurons, controls histamine-induced communication through calcium-dependent autoinhibition with implications for anaphylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Allergen-induced activation of mast cells could lead to alterations in the function of afferent neurons like intrapulmonary airway C-fiber ( 45 ), neurons within the CNS ( 46 , 47 ), and somatosensory itch fiber in the skin ( 48 ), sensory nerve excitability ( 49 ) and neuroplasticity ( 50 ), increases in synaptic efficacy in autonomic ganglia ( 51 , 52 ) and stimulation of enteric neurons ( 53 , 54 ) – an effect which might be more prominent in atopic individuals compared to non-atopic controls ( 44 ). Of note, a recent neuronal receptor-based controlling mechanism of anaphylaxis involving the glutamatergic receptor mGluR7was described ( 55 ). These data would therefore be consistent with our hypothesis that upregulation of neuroinflammatory signalling pathways might impact neuromodulation in anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-induced activation of mast cells could lead to alterations in the function of afferent neurons like intrapulmonary airway C-fiber ( 45 ), neurons within the CNS ( 46 , 47 ), and somatosensory itch fiber in the skin ( 48 ), sensory nerve excitability ( 49 ) and neuroplasticity ( 50 ), increases in synaptic efficacy in autonomic ganglia ( 51 , 52 ) and stimulation of enteric neurons ( 53 , 54 ) – an effect which might be more prominent in atopic individuals compared to non-atopic controls ( 44 ). Of note, a recent neuronal receptor-based controlling mechanism of anaphylaxis involving the glutamatergic receptor mGluR7was described ( 55 ). These data would therefore be consistent with our hypothesis that upregulation of neuroinflammatory signalling pathways might impact neuromodulation in anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study by Wu et al showed that calpain 1 contributes to mast cell degranulation (96). Furthermore, inhibition of mGluRs, known to regulate histamine (34), abolished the anti-PrP antibody toxic effects (28). Taken together and in addition to the allergenic-related proteins associated with ICSM35 treatment reported by Tayebi and colleagues (21), this provides sufficient evidence to investigate the allergenic pathways potentially induced by treatment with anti-PrP antibodies which we refer to as "IgG-Mediated Neuronal Hypersensitivity".…”
Section: Discussionmentioning
confidence: 99%
“…PGs are synthesized by the cyclooxygenase (COX) enzymes in the arachidonic acid metabolic pathway and have been shown to play an important role in hypersensitivity (33). The neuronexpressed mGluR7 was shown to regulate histamine and ablation of mGluR7 in mice led to anaphylaxis (34). Of importance, mGluR7-interactors; mGluR1 and mGluR5 were shown to form complexes with PrP C and their pharmacological inhibition cancelled the 'neurotoxic' effects caused by anti-PrP antibodies (28).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study by Wu et al showed that calpain 1 contributes to mast cell degranulation [98]. Furthermore, inhibition of mGluRs, known to regulate histamine [34], abolished the anti-PrP antibody toxic effects [28]. Taken together and in addition to the allergenic-related proteins associated with ICSM35 treatment reported by Tayebi and colleagues [21], this provides su cient evidence to investigate the allergenic pathways potentially induced by treatment with anti-PrP antibodies which we refer to as "IgG-Mediated Neuronal Allergenic Toxicity".…”
Section: Discussionmentioning
confidence: 99%